B44 The Cns-heart Axis Is A Source Of Cardiac Dysfunction In Mouse Models Of Huntington's Disease. (17th September 2014) - Mielcarek, M; Inuabasi, L; Bondulich, MK; Muller, T; Osborne, GF; Franklin, SA; Smith, DL; Neuder, A; Rosinski, J; Rattray, I; Protti, A; Bates, GP
Abstract : Cardiac remodelling and contractile dysfunction occur during both acute and chronic disease processes including the accumulation of insoluble aggregates of misfolded amyloid proteins that are typical features of Alzheimer's, Parkinson's and Huntington's disease (HD). while HD has been described mainly as a neurological disease, multiple epidemiological studies have shown that hd patients exhibit a high incidence of cardiovascular events leading to heart failure, and that this is the second highest cause of death. Given that huntingtin is ubiquitously expressed, cardiomyocytes may be at risk of an HD-related dysfunction. In mice, the forced expression of an expanded Polyq repeat under the control of a cardiac specific promoter led to severe heart failure followed by reduced lifespan. However the mechanism leading to cardiac dysfunction in the clinical and pre-clinical hd settings remains unknown. To unravel this mechanism, we employed the R6/2 transgenic and HdhQ150 knock-in mouse models of hd. we found that pre-symptomatic animals developed connexin-43 relocation and a significant deregulation of hypertrophic markers and bdnf transcripts. In the symptomatic animals, pronounced functional changes were visualised by cardiac mri revealing a contractile dysfunction, which might be a part of dilatated cardiomyopathy (dcm). This was accompanied by the re-expression of foetal genes, apoptotic cardiomyocyte loss and a moderate degree of interstitial fibrosis. To our surprise, we could identify neither mutant htt aggregates in cardiac tissue nor a hd-specific transcriptional dysregulation, even at the end stage of disease. We postulate that the hd-related cardiomyopathy is caused by altered central autonomic pathways although the pathogenic effects of mutant htt acting intrinsically in the heart may also be a contributing factor.